A Method To Prepare An Economic Substitute For Agarose Gel Along With A Low-Cost Electrolyte For Functional DNA Gel Electrophoresis - Kamar Shayah; Joseph Shenekji; Ahmad Richi; Yaman Diwan; Aya Koja (Syrian Journal for Science and Innovation)
The use of agarose in electrophoresis is indispensable in modern biotechnology research. However, agarose is relatively expensive and not available in limited-budget scientific institutions, labs and educational facilities. Therefore, the search for more economical and available alternatives for researchers in developing countries and different educational institutions was urgently needed. This study was conducted on several alternatives to agarose gel, including animal gelatin, microbiological grade agar-agar, wheat starch and a mixture of animal gelatin and agar-agar. The study focused on food grade agar-agar to find a suitable alternative to agarose with appropriate treatment with NaCl, NaHCO₃, and NaOH, and different parameters of comparison were documented to see which alternative gave the best results. In addition to the agarose substitute and to make a more approachable method for labs on a tight budget, an alternative to electrolyte to TBE or TAE was used, consisting of NaCl and NaHCO₃ and NaOH and water in a very precise percentage to give PH= 9.1. To test the manufactured Gel in this method, DNA samples were loaded, and the gel result of separation using treated food grade agar-agar showed results compared to agarose gel in the same standards, and the process of using it was relatively simple and similar to that of agarose. This electrophoresis method costs 15 times less than industrial-grade agarose and TBE or TAE and could increase the scale of research in the field of biotechnology applications and education.